2000
DOI: 10.1161/01.str.31.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Exacerbates and Estrogen Replacement Attenuates Photothrombotic Focal Ischemic Brain Injury in Rats

Abstract: Background and Purpose-We previously reported the infarct volumes in female spontaneously hypertensive rats (SHR) to be significantly smaller than those in male SHR. The purpose of the present study was to determine whether estrogen is responsible for the sex difference in ischemic vulnerability in SHR. Methods-In experiment 1, 1 week (short-term) or 4 weeks (long-term) after the ovariectomy (OVX), female SHR (5 months old) were randomly subjected to photothrombotic occlusion of the middle cerebral artery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…In particular, several investigators have examined the efficacy of 17␤-estradiol in models of stroke (Alkayed et al, 1998aCarswell et al, 2004;Dubal et al, 1998;Fukuda et al, 2000;Hurn et al, 1995;McCullough et al, 2001;Toung et al, 1998;Yang et al, 2000). Hurn and colleagues (1995) first described in a model of global cerebral ischemia the effects of chronic 17␤-estradiol treatment.…”
Section: Gendermentioning
confidence: 99%
“…In particular, several investigators have examined the efficacy of 17␤-estradiol in models of stroke (Alkayed et al, 1998aCarswell et al, 2004;Dubal et al, 1998;Fukuda et al, 2000;Hurn et al, 1995;McCullough et al, 2001;Toung et al, 1998;Yang et al, 2000). Hurn and colleagues (1995) first described in a model of global cerebral ischemia the effects of chronic 17␤-estradiol treatment.…”
Section: Gendermentioning
confidence: 99%
“…Estradiol benzoate (Sandstrom and Rowan, 2007), estradiol valerate (Fukuda et al, 2000), and conjugated equine estrogens (LittletonKearney et al, 2005;McCullough et al, 2001;Rusa et al, 1999) were administered in altogether five studies, all showing protective effects.…”
Section: Type Of Estrogenmentioning
confidence: 99%
“…In vitro studies indicate that estrogens increase the viability and differentiation of primary cultures from different neuronal populations from the hypothalamus, amygdala, neocortex, or hippocampus. Numerous in vivo studies have also demonstrated the neuroprotective effects of estrogens in a variety of animal stroke models, including transient and permanent middle cerebral artery occlusion Alkayed et al, 1998;Dubal et al, 1998), global forebrain ischemia (Sudo et al, 1997), photothrombotic focal ischemia (Fukuda et al, 2000), glutamate-induced focal cerebral ischemia (Mendelowitsch et al, 2001), and subarachnoid hemorrhage (Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%